Multiscale failure and damage analysis of sheet molding compound (SMC) composites using Micro-CT image-based reconstruction model. (15th February 2022) - Lim, Hyoung Jun; Choi, Hoil; Yun, Gun Jin
Abstract: This paper presents a multiscale failure and damage analysis methodology for sheet molding compound (SMC) composites through a new bundle packing reconstruction algorithm and complete failure and damage constitutive modeling. Due to the complex flow pattern during the compression molding process, the SMC composites are featured by a spatially varying distribution of fiber bundles. The novel bundle reconstruction algorithm can generate representative volume element (RVE) mesostructure models considering the statistical fiber bundle orientation and dispersion based on image analysis of actual SMC composites. In particular, statistical bundle dispersions are investigated in-depth, which has not yet been considered in damage analysis of SMC composites. Moreover, constitutive modeling of constituents is implemented for simulating various local damage such as bundle failure, cohesive damage, and matrix damage observed in SMC composites. The effects of the statistical mesostructure heterogeneities on the failure and damage behavior are discussed through a series of failure analyses. Finally, the simulation results are experimentally validated through a tensile test and actual inspection results by X-rays, 3D imaging, and scanning electron microscope (SEM).